From Internet Access to Internet Skills: Digital Inequality among Older Adults - Hargittai, Eszter; Piper, Anne Marie; Morris, Meredith Ringel (Universal Access in Information Society, 2018)
Although much research examines the factors that affect technology adoption and use, less is known about how older adults as a group differ in their ability to use the Internet. The theory of digital inequality suggests that even once people have gone online, differences among them will persist in important ways such as their online skills. We analyze survey data about older American adults’ Internet skills to examine whether skills differ in this group and if they do, what explains differential online abilities. We find that there is considerable variation in Internet know-how and this relates to both socioeconomic status and autonomy of use. The results suggest that attempts to achieve a knowledgeable older adult population regarding Internet use must take into account these users’ socioeconomic background and available access points.